Does intention to recommend HPV vaccines impact HPV vaccination rates? - Feemster, Kristen A (Hum Vaccin Immunother, 2014)
Despite recommendations for routine vaccination, HPV vaccination rates among adolescent females have remained low. The objective of this prospective cohort study was to determine whether clinician intention to recommend HPV vaccines predicts HPV vaccine series initiation among previously unvaccinated 11 to 18 year-old girls (N = 18,083) who were seen by a pediatric clinician (N = 105) from a large primary care network within 3 years of vaccine introduction. We used multivariable logistic regression with generalized estimating equations, Cox Regression and standardized survival curves to measure the association between clinician intention and time to and rate of first HPV vaccine receipt among eligible females. All models adjusted for patient age, race / ethnicity, payor category, visit type, and practice location. Eighty-5 percent of eligible 11 to 12 year-old and 95% of 13 to 18 year-old girls were seen by a provider reporting high intention to recommend HPV vaccines. However, only 30% of the cohort initiated the HPV vaccine series and the mean number of days from first eligible visit to series initiation was 190 (95% C.I. 184.2, 195.4). After adjusting for covariates, high clinician intention was modestly associated with girls’ likelihood of HPV vaccine series initiation (OR 1.36; 95 % C.I. 1.07, 1.71) and time to first HPV vaccination (HR 1.22; 95% 1.06, 1.40). Despite high intention to vaccinate among this cohort of pediatric clinicians, overall vaccination rates for adolescent girls remained low. These findings support ongoing efforts to develop effective strategies to translate clinician intention into timely HPV vaccine receipt.